Apples and Oranges: The Logic of the Early and Later Arabic Logicians - Spevack, Aaron (Islamic law and society, 2010)
Abstract In a recent article in Islamic Law and Society, Khaled El-Rouayheb proposed that opposition to logic was probably never the predominant view of Sunni Muslim scholars. El-Rouayheb also expressed doubt in the position of later scholars who argued that there existed two approaches to the study of logic, one whose permissibility was debated, and another whose permissibility was agreed upon. In response to El-Rouayheb, Mufti Ali argued in his own article that opposition to logic was the predominant view of Sunni Muslim scholars between the thirteenth and fifteenth centuries. In this article, I argue, pace Ali, that there is merit to the claim that neither opposition to, nor support for, logic achieved predominance, especially between the thirteenth and fifteenth centuries, even if favorable opinions came to be viewed as the soundest position in later centuries. I also argue, pace El-Rouayheb, that there is merit to the proposition that there are two distinct approaches to logic, one that mixes objectionable elements from Greek philosophy, and one that, in varying degrees, may have rid itself of these elements. Additionally, I argue that the thirteenth through fifteenth centuries may have marked a transitional period during which the two approaches became more distinct, although some jurists who ruled on logic did not always notice, or acknowledge, the distinction.